PENGARUH CEO NARCISSISM DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - MUHAMMAD HISYAM; ANNISA KANTI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to obtain empirical evidence regarding how the influence of CEO Narcissism and other variables such as Board of Size, Female Directors, Financial Distress, Company Size, and Insitutional Ownership on Tax Avoidance. The Measurement of Tax Avoidance variables is carried out using the Effective Tax Rate (ETR). This study used a sample of 141 manufacturing companies that were consistently listed on the Indonesia Stock Exchange (BEI) during the period 2022-2024. Through the purposive sampling method, this study produced 423 data that met the research criteria. All data were tested and analyzed using multiple regression analysis techniques. The results of this study indicate that CEO Narcissism, Board of Size, Female Directors, Financial Distress, and Company Size have an effect on Tax Avoidance. Meanwhile, other variables, namely Institutional Ownership have no effect on Tax Avoidance.